PEDAGOGICAL OPPORTUNITIES FOR DEVELOPING GENDER SELF-AWARENESS SKILLS IN ADOLESCENT STUDENTS (Scientific journal of the Fergana State University, 2023)
The article analyzes the features of the formation of immunity to "popular culture" among adolescent schoolchildren on the basis of a gender approach. It considers adolescence as a difficult, conflict period, and the development of self-awareness and self-esteem during this period.